2020
DOI: 10.1016/j.brainres.2019.146532
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping spectrums: The clinicogenetic commonalities between Charcot-Marie-Tooth and other neurodegenerative diseases

Abstract: Charcot-Marie-Tooth (CMT) disease is a progressive and heterogeneous inherited peripheral neuropathy. A myriad of genetic factors have been identified that contribute to the degeneration of motor and sensory axons in a length-dependent manner. Emerging biological themes underlying disease include defects in axonal trafficking, dysfunction in RNA metabolism and protein homeostasis, as well deficits in the cellular stress response. Moreover, genetic contributions to CMT can have overlap with other neuropathies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 270 publications
(324 reference statements)
0
4
0
1
Order By: Relevance
“…A recently characterized subtype, CMT6C, was identified in two families from our cohort, associated with homozygous mutations in PDXK (under publication; Dr. Delague). Additionally, CMT patients in this study were observed with mutations in BAG3, DNAJB2, MTMR4, and VRK1 (under publication; Dr. Delague); CMT genotype-phenotype correlations with variants in BAG3 and DNAJB2 genes were recently described [63,64]. Our cohort also included CMT4B3 patients presenting with unique syndromic features.…”
Section: Charcot-marie-tooth Diseasementioning
confidence: 96%
“…A recently characterized subtype, CMT6C, was identified in two families from our cohort, associated with homozygous mutations in PDXK (under publication; Dr. Delague). Additionally, CMT patients in this study were observed with mutations in BAG3, DNAJB2, MTMR4, and VRK1 (under publication; Dr. Delague); CMT genotype-phenotype correlations with variants in BAG3 and DNAJB2 genes were recently described [63,64]. Our cohort also included CMT4B3 patients presenting with unique syndromic features.…”
Section: Charcot-marie-tooth Diseasementioning
confidence: 96%
“…A number of inherited variants and de novo mutations have been identified in human KIF1A from clinical studies. These mutations have been linked to neurodevelopmental and neurodegenerative disorders including spastic paraplegias, encephalopathies, intellectual disability, autism, and sensory neuropathies (3,(10)(11)(12)(13)(14)(15). For KIF1A-associated neurological disorder (KAND), the mutations span the entirety of the KIF1A protein sequence; the majority are located within the kinesin motor domain (aa 1-369) and…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have described two novel compound heterozygous missense mutations in the VRK1 gene, in two siblings, from a non-consanguineous Lebanese family, affected with a distal hereditary motor neuropathy (dHMN), associated with upper motor neuron signs (El-Bazzal et al, 2019). Diseases due to mutations in VRK1 , that we regrouped under the name of “ VRK1-related motor neuron diseases”, illustrate very well the clinical overlap which exists between CMT/dHMN and diseases affecting upper and/or lower motor neuron diseases, such as hereditary spastic paraplegias, Amyotrophic Lateral Sclerosis and Spinal Muscular Atrophy (Hanemann & Ludolph, 2002; Irobi et al, 2006; Martin, Hicks, Holbrook, & Cox, 2020; Rossor, Polke, Houlden, & Reilly, 2013; Timmerman, Clowes, & Reid, 2013).…”
Section: Introductionmentioning
confidence: 85%